HIGH CONTEXT CULTURE ANALYSIS IN “SANAM TERI KASAAM” MOVIE - Vera Tri Romadhani (Universitas Madura, 2019)
The aims of this research is to find out the kinds and the meanings of high context culture in sanam teri kasaam movie, to give understanding about culture in india and culture that include into high context culture through movie. Movie is also called a film. Movie can be done well during the shooting. And the point of view of this research is for communication, it means that we will know the other culture, we haven’t to come to that country directly but with this research we can know the culture in that country.This research observed all the characters and have found four parts of high context culture . From the characters of sanam teri kassam movie, those are Body language (Kinesics) which include gesture, facial expression, and dress. Second is eye contact (Oculistics), Then Touch (Haptics) and the last is Body distance (proxemics). So that, High context culture is a large part of the meanings lies in the physical context. As a result, the message itself carries less information.